Strengthening system using post-tension tendon with an internal anchorage of concrete members. (1st October 2016) - Mimoto, Tatsuhiko; Sakaki, Takuya; Mihara, Takafumi; Yoshitake, Isamu
Graphical abstract: Highlights: A new strengthening system for concrete members is developed. A prestressing tendon is anchored into the wedge-hole filled with mortar. Adequate load-bearing capacity of the anchorage is confirmed. Bond effect of the prestressing tendon is examined by FE simulation. Abstract: The present study aims to develop a strengthening system using prestressing tendons embedded into an internal anchorage of concrete member. The internal anchorage, a wedge-shaped hole, is made by using a special drilling machine. The tip of the hole is filled with high strength mortar to anchor firmly the prestressing tendon. The strengthening system is acceptable even in relatively narrow workspaces, and also applicable for joints between existing and additional concrete members. The experimental study conducted a pull-out test of the prestressing tendon to examine the load-bearing capacity. A finite element simulation was also performed to confirm the bonding and unbonding effects of the prestressing tendon. The test result confirms adequate load-bearing capacity of the anchorage for the prestressing tendon. In addition, the FE simulation shows that the strengthening system can provide a constant prestress even if the prestressing tendon is not bound to the mortar in the anchorage.